МЕКТЕП ЖАСЫНДАҒЫ БАЛАЛАРДЫҢ ПСИХОФИЗИОЛОГИЯЛЫҚ ЕРЕКШЕЛІКТЕРІ (Experimental biology, 2015)
Investigation of short term and long term visual memory, physiological indices of mental efficiency demonstrated significant age distinction.
Keywords: physiological indices